PENGARUH BUDAYA KERJA DAN ALUR REKAM MEDIK TERHADAP KEPUASAN PASIEN DI PUSKESMAS KERTOSONO - Agnis Rindha Pavilonita (Universitas Islam Kadiri, 2019)
This research was conducted at Puskesmas Kertosono Nganjuk Regency. The objectives to be achieved in this research is to describe the work culture and medical record system on patient satisfaction at Puskesmas Kertosono with patient respondents who visited to Pukesmas amounted to 84253 in 2016. This research is included in survey research method, that is a research conducted without intervention Against research subjects (community). This research design using descriptive quantitative method. The sampling technique used was accidental sampling with 398 respondents. While the analysis technique using descriptive analysis and multiple linear regression analysis. The result of data analysis showed partially work culture and the flow of medical record have a significant effect on patient satisfaction and work culture have the most dominant effect on patient satisfaction compared with other variable. Regression analysis showed that together independent variables consisting of work culture and medical record flow have a significant effect on patient satisfaction. This means that if the work culture of the officers and the flow of medical records are increased together it will have an impact on increasing patient satisfaction and vice versa worker culture and medical record flow decreases together it will lead to decreased patient satisfaction.